HBR Guide to Thinking Strategically - Harvard Business Review (Boston, Massachusetts : Harvard Business Review Press, 2019)
The HBR Guide to Thinking Strategically provdes practical advice and tips to help you see the big-picture perspective in every aspect of your daily work, from making decisions to setting team priorities to attacking your own to-do list. You'll learn how to: Understand your organization's strategy. - Align your team around key objectives. - Focus in the priorities that matter most. - Spot trends in your company and in your industry. - Conside future outcomes when making decisions. - Manage trade-offs. - Embrace a leadership mindset
Tặng
Keywords: Strategic planning; Business planning; Industrial Management